Effect of Oral Erythropoietin in Prevention of Anemia of Prematurity (Bangladesh Journal of Child Health, 2018)
Introduction: Anemia of prematurity (AOP) is a common problem of very low birth weight babies. Blood transfusion is a necessity when it occurs in moderate to severe form putting the child in to the risk of transfusion related complications. Erythropoietin, a potent stimulator of hemopoesis is available in breast milk in good amount and absorbed intact under physiologic condition. In this background oral recombinant human erythropoietin (rhEPO) can be a useful alternative to its subcutaneous administration in prevention of AOP.Objective: To evaluate the efficacy of oral rhEPO in the prevention of AOP in very low birth weight (VLBW) neonates.Methods: This randomized controlled study conducted in the NICU of BSMMU over one year. Total 60 preterm (